Microparticle, Conductivity, and Density Measurements from the WAIS Divide Deep Ice Core, Antarctica - Kreutz, Karl; Hamilton, Gordon S.; Breton, Daniel; Koffman, Bess (IEDA: US Antarctic Program Data Center, 2011)
Abstract: This data set includes microparticle concentration, electrical conductivity, and density measurements from the West Antarctic Ice Sheet (WAIS) Divide deep ice core, WDC06A. Microparticle concentration data are reported as total particles per ml of meltwater. Concentration was measured using a laser detector and the University of Maine WAIS Melt Monitor system. Conductivity is measured in micro-Siemens per cm (uS/cm). Density data were collected on 3 by 3 by 100 cm sticks from the WDC06A core, using the Maine Automated Density Gauge Experiment (MADGE). Density data span 0 to 160 m in depth, while the particle and conductivity measurements span the upper 577 m of the core. Data are available via FTP in ASCII text format (.txt).